The Dynamics of Public Policy-Making in Public Administration: From Classical Management to the New Public Administration - Abdul Rahman; Septi Wulandari; Komang Ema Marsitadewi; Teresa Irmina Nangameka; Shelda Adriana Taimaris Rogi (Journal of Contemporary Governance and Public Policy, 2026)
This article examines how public administration shapes policy-making. Scholarship typically treats Classical Management, Neo-Classical Management, and New Public Administration (NPA) as successive stages, while policy studies often analyse decision-making, participation, and implementation separately. Consequently, literature lacks an integrated account of how shifting administrative logics structure policy-making and contribute to persistent governance challenges. Drawing on a systematic literature review guided by PRISMA, the study analyses 23 peer-reviewed, Scopus-indexed articles. Rather than aggregating empirical effects, it uses thematic coding to examine policy-making dynamics across paradigms, from Classical Management to NPA. Findings show each paradigm embodies a distinct logic: hierarchical technocratic control in the classical model; behaviourally informed but administratively managed decision-making in the neo-classical model; and collaborative, reflexive governance in the NPA model. Paradigms coexist rather than replace one another. In the Global South, although NPA principles support SDG 16.6 and 16.7, implementation is constrained by neo-classical reforms and residual classical bureaucracies, limiting participatory engagement envisaged by SDG 16.8. Effective governance reform requires aligning institutional capacity with participatory processes rather than adopting a new paradigm.